2015
DOI: 10.1021/jp509819z
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Dexter–Silverton Type Manganese Heteropolytungstate [Mn7(MnW12O42(OH)4·8H2O)] Hollow Microsphere: Synthesis, Crystal Structure, Growth Mechanism, and Optical Property Study

Abstract: An uncommon yet highly symmetric crystal form of a Mn-based heteropolytungstate (Mn-HPT), Mn 7 (MnW 12 O 42 (OH) 4 )• 8H 2 O, has been synthesized by a unique solvothermal method at 180 °C for 6 h. The nature of the solvent (water/ethanol = 50/50 by volume) and the presence of citric acid were the key reasons for the formation of the Mn-HPT phase and its hollow spherical morphology under the said experimental conditions. Combined powder X-ray diffraction analysis and field emission scanning electron miroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The X‐ray diffraction (XRD) pattern of the Ni M ‐POM/Ni (Figure a) showed the standard diffraction patterns of the Dexter–Silverton POM of [M 8 W 12 O 42 (OH) 4 (H 2 O) 8 ] (database no. ICDD‐PDF‐80–1525) . Furthermore, a representative sample of NiCo‐POM/Ni was studied by high‐resolution transmission electron microscopy (HRTEM, Figure b) and showed lattice fringes with interplanar distances of 0.34 and 0.38 nm, respectively, corresponding to the (1 2 3) and (2 2 2) planes of NiCo‐POM.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The X‐ray diffraction (XRD) pattern of the Ni M ‐POM/Ni (Figure a) showed the standard diffraction patterns of the Dexter–Silverton POM of [M 8 W 12 O 42 (OH) 4 (H 2 O) 8 ] (database no. ICDD‐PDF‐80–1525) . Furthermore, a representative sample of NiCo‐POM/Ni was studied by high‐resolution transmission electron microscopy (HRTEM, Figure b) and showed lattice fringes with interplanar distances of 0.34 and 0.38 nm, respectively, corresponding to the (1 2 3) and (2 2 2) planes of NiCo‐POM.…”
Section: Resultssupporting
confidence: 84%
“…Notably,aweak peak at 2.6 was assigned to Co(2) coordination with OH anions( bond distance 3.08 ) ( Figure 4a). [32,39,40] Furthermore, the XANES fitting of Dexter-Silverton NiCo-POM/Ni indicated that the Co centres were six-coordinate and occupied the nearly octahedral environment in the NiCo-POM/Ni.B ased on the XPS, XANES and ICP-AES data ( The NiM-POM/Ni composites were investigated as electrocatalysts for HER in alkaline aqueous KOH as electrolyte. In order to evaluatethe HER performance of the Ni-POM/Ni, NiCo-POM/ Ni, NiZn-POM/Ni,a nd NiMn-POM/Ni,atypicalt hree-electrode system in an N 2 -saturated 1.0 m KOH aqueous solution was applied by using the correspondingc omposites as working electrodes, as aturated calomel electrode as reference electrode and ac arbon rod as counter electrode.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…After that, star-shaped Keggin-type heteropolytungstate was obtained as catalyst for preparing quinoline derivatives [ 14 ]. From then on, Chattopadhyay’s and co-workers discovered the Dexter-Silverton type molybdenum tungstate of hollow microspheres [ 15 ]. For the past years, ours group has been working on the control-synthesis and functionalization of POM-based nano/micromaterials by chemical precipitation or hydrothermal methods [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%